Language socialization in bilingual and multilingual societies - Bayley, Robert, 1943-; Schecter, Sandra R. (Bilingual education and bilingualism, 2003)
An exploration of language socialization from very early childhood through to adulthood. It discusses educational and sociological issues, covering not only often-studied communities in Canada and the United States, but also Australia, Bolivia, Egypt, India and Slovakia.